SPECIAL EDUCATION IN COUNTRYSIDE SCHOOLS - UNVEILING POLICIES AND EDUCATIONAL MANAGEMENT FRONT OF THE SERVICE OF STUDENTS WITH DISABILITIES IN THE MUNICIPALITY OF BOM JESUS DA LAPA - BA - Francisca de Jesus Cangirana, Sandra; Ricardo Pereira de Almeida Braga, Luiz (Revista Gênero e Interdisciplinaridade, 2022)
The education of the field is that appropriate to the local characteristics both related to production systems and the way of life, within the perspective of inclusion, it is verified that to have in the schools of the field actions that contemplate the uniqueness of students of special education, in the field, it is important to ensure their visibility, through public policies. This work aims to describe and analyze public policies and educational management in the face of the care of students with disabilities in the field, permeating historical aspects of field education and special education, the difficulties encountered for offering an inclusive education in rural schools, as well as the dismay in relation to the offer of access to basic education at all levels, whether by people with disabilities or not. This article was constructed from a field research, which used the qualitative approach and the deductive method to expose descriptive-argumentative assumptions formulated from a bibliographic and its confrontation with the results of the application of questionnaires to the general coordinator of Special Education of the municipality of Bom Jesus da Lapa and to the managers of schools in the field of this field, whose schools, have rooms of Multifunctional Resources with specialized educational care (AEE). In this research, it was verified that the policies related to inclusion go beyond the work of the teacher in the classroom and school management, relating to all the actors involved in the educational system.